PHYSICAL TRAINING IN ATHLETES: ANALYSIS OF CARDIAC AUTONOMIC MODULATION - Araújo,Matheus Karia (2021)
ABSTRACT Introduction Cardiac autonomic modulation (CAM) is a result of the balance between the sympathetic and parasympathetic systems. This interaction results in heart rate variation (HRV), analyzed by specific electrocardiographic parameters. These parameters are modified by the practice of physical activity, indicating better cardiac conditioning. Objectives To evaluate the cardiac autonomic modulation of athletes of the XXVIII Ecological Walk at two separate times during their period of physical training. Also, to link the practice of physical activity with stress reduction in these individuals. Methods 24-hour Holter exams were performed at two times (before and after a 2-month period of non-standard physical training), and the results were analyzed using the software programs Epi-Info 7 and BioEstat 5.0. Inferential analysis was performed by the nonparametric Shapiro-Wilk test. Statistical significance was assigned to p values less than 0.05, with 95% confidence interval (95% CI). Results The sample was mostly male (n = 14; 77.78%), with a mean age of 49.55 years. No individual trained for less than 60 days; most (47.06%) trained for 151-200 days, with walking being the predominant modality (64.71%). No statistically significant difference was found in the parameters HRV pNN50 (p = 0.18), rMSSD (p = 0.14) or HF (p = 0.117) after the evaluated training period. Conclusions Participants who are longtime sportsmen and physically active showed parasympathetic saturation, therefore, they did not show significant changes in HRV. Also, low levels of stress were observed in those who practiced physical activity. Level of evidence II; Prognosis Study.